Countries of the world and their leaders yearbook 2010 - Gale Group (Detroit, Mich. Gale, 2009)
A compilation of U.S. Department of State reports on contemporary political and economic conditions, government personnel and policies, political parties, religions, history, education, press, radio and TV, climate, and other characteristics of selected countries of the world; together with travel alerts, passport and visa information, world health information for travelers, and customs and duty tips for returning residents.
v.1. Status of the world's nations, Background notes: Afghanistan-Mozambique -- v.2. Background notes: Namibia-Zimbabwe, International treaty organizations, Foreign travel.
"ISSN 0196-2809".
Electronic reproduction.
Keywords: Geography; International travel regulations; Statesmen; World history; World politics; Electronic books